2021
DOI: 10.1007/s40120-021-00305-9
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Migraine in Japan: Results of the ObserVational Survey of the Epidemiology, tReatment, and Care Of MigrainE (OVERCOME [Japan]) Study

Yasuhiko Matsumori,
Kaname Ueda,
Mika Komori
et al.

Abstract: Introduction The ObserVational survey of the Epidemiology, tReatment, and Care Of MigrainE study in Japan (OVERCOME [Japan]) assessed the impact and burden of migraine in Japan. Methods OVERCOME (Japan) was a cross-sectional, observational, population-based web survey of Japanese people with migraine conducted between July and September 2020. The burden and impact of migraine were assessed using the Migraine Disability Assessment (MIDAS), Migraine-Specific Quality-of-Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 33 publications
5
65
0
Order By: Relevance
“…Our findings show that impact of migraine attacks, as measured by the HIT-6, migraine frequency and headache frequency were each uniquely associated with interictal burden. Previous studies have also shown a positive, albeit weaker, association between interictal burden and migraine/headache frequency [ 27 , 28 ]. This study showed a positive association between ictal disability (HIT-6) and interictal burden (MIBS-4) but did not explore specific biological or clinical drivers of interictal burden.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that impact of migraine attacks, as measured by the HIT-6, migraine frequency and headache frequency were each uniquely associated with interictal burden. Previous studies have also shown a positive, albeit weaker, association between interictal burden and migraine/headache frequency [ 27 , 28 ]. This study showed a positive association between ictal disability (HIT-6) and interictal burden (MIBS-4) but did not explore specific biological or clinical drivers of interictal burden.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine and tension-type headache (TTH) are included as primary headaches in the International Classification of Headache Disorders 3rd edition (ICHD-3) [ 3 ], and they are the main types of primary headaches. In Japan, the overall prevalence of migraine is 6.0–8.4%, and 74.2% of them complain that migraine headache impairs their daily activity significantly [ 4 – 7 ]. A previous study shows that Japanese migraine patients have an incremental burden compared to non-migraine patients in terms of decreased health-related quality of life, impaired productivities, more healthcare providers visits, and higher indirect costs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2 representative headaches are migraine and tension-type headache (TTH), and they are described in the International Classi cation of Headache Disorders 3rd edition (ICHD-3) [3]. Migraine impacts the quality of life, familial relationships, and work productivity [4]. In Japan, the total prevalence of migraine is 4.3-8.6% [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Migraine impacts the quality of life, familial relationships, and work productivity [4]. In Japan, the total prevalence of migraine is 4.3-8.6% [4][5][6][7][8]. The economic and social impacts of migraine on productivity are starting to be recognized [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation